Comparison of health‐related quality of life and emotional distress among Chinese cancer survivors. Issue 3 (4th June 2013) - So, Winnie KW; Ling, Gigi CC; Choi, Kai‐chow; Chan, Carman WH; Wan, Rayman WM; Mak, Suzanne SS; Sit, Janet WH
<x xml:space="preserve">Abstract</x> The purpose of this study is to compare health‐related quality of life (HRQoL) and emotional distress among diverse cancer survivors who had completed all treatment within the previous year. A convenience sample of 353 cancers survivors (lung, head and neck, breast and prostate cancers) were recruited to complete a survey, which consisted of (i) Hospital Anxiety and Depression Scales; (ii) Chinese version of the Functional Assessment of Cancer Therapy—General version; and (iii) demographic and clinical data. The HRQoL scores were similar among the four types of survivors. Mild anxiety and depression levels were reported, but no significant difference was noted. Younger females with financial burdens and uncertain prognosis were particularly associated with HRQoL and emotional distress. Further studies are essential to identify specific problems that cancer patients experience after cancer diagnosis that might lead to the early detection of those most at risk of ongoing problems.